The Implementation of Project-Based Learning Method in Teaching ESP (English for Specific Purposes): Case Study - Andanty, Ferra Dian (Penerbit STKIP PGRI Bangkalan, 2020)
This study attempts to perform how Project Based Learning Method is conducted in English for Specific Purposes (ESP) program. It was implemented in ESP program for 8th semester pre-service teachers in English Language Education Department in Universitas PGRI Adi Buana Surabaya. Teaching ESP should be given both theoretically and practically and Project Based Learning method can be applied as effective way for teaching and learning process in ESP program that besides students study the theory, they also design the project to apply the theory of ESP they have already studied. In ESP program, the students are assigned to make course books design for several fields of study and practice one of unit materials in front of the class. The books are designed based on the needs of target language which are gained by having interview and observing the target situation. Giving students the book project enables them to boost and stimulate their sense of creativity in creating an ESP course book. However, the lecturers’ assistance is important for reducing students’ confusion in deciding practices in the book.